Studi Konduktivitas Panas pada Papan Partikel - - Ramadlan; Ahmad Syuhada; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2013)
The purpose of this study is to determine the effect of variations in the use of fillers for particle board. Various composition of fillers from rice husk and wood sawdust were mixed with synthetic glue matrix of PVAC (Poly Vinyl Acetate Co-Acrylic) and port land cement to produce the particle board. Their effects to the thermal conductivity of particle board (fiberboard) is analyzed. Four walls of particle boards of 25 cm2 were installed in the specialy prepared test apparatus. The measurements were conducted for the surface temperature outside and inside with the measurement interval of 70 minutes. From the results of measurements, the smallest thermal conductivity property is given by kayu jati sawdust with a conductivity of 0.020 W/m0C. Rice husk particle board has a conductivity of 0.024 W/m0C, while the highest conductivity is given by rice husk bran particle board, which is 0042 W/m0C.